Respuesta :

ANSWER:

m = -3/4

b = -3

[tex]y=-\frac{3}{4}x-3[/tex]

STEP-BY-STEP EXPLANATION:

We have that the equation in its slope-intercept form is the following:

[tex]\begin{gathered} y=mx+b \\ \text{where m is the slope and b is y-intercept} \end{gathered}[/tex]

We calculate the slope as follows:

[tex]m=\frac{y_2-y_1}{x_2-x_1}[/tex]

To calculate the slope we use the intercepts that are (-4, 0) and (0, -3), we replace:

[tex]m=\frac{-3-0}{0-(-4)}=\frac{-3}{4}=-\frac{3}{4}[/tex]

Now, the value of b would be -3, since the y-intercept is (0,-3), therefore, the equation would be:

[tex]y=-\frac{3}{4}x-3[/tex]